Structured professional judgement of risk in forensic psychiatric practice - Richardson, Clare Louise (2009)
The central issue addressed in this thesis was the validation of a novel risk assessment system designed to meet the security requirements of a high secure forensic hospital. To this end, three research strands investigating the clinical, predictive and preventative utility of the system were pursued. This thesis reports the process of the development, adaptation and implementation of a system based on the HCR-20, called the Structured Clinical Judgement: Risk (SCJ: Risk). The first research strand involved investigation of the processes necessary implement a system of structured professional judgement. The conceptual and operational utility of the system were investigated, and successful implementation of the system within clinical practice was demonstrated by compliance of use by clinical teams. A survey was conducted, investigating the perceptions of clinicians in relation to the clinical utility and usability of the SCJ: Risk. Overall acceptance of the pilot and implementation phase of the system was demonstrated, and the system was perceived to assist clinical teams to structure and document risk-related decisions. The second research strand studied the validity of the SCJ: Risk in predicting intra-institutional behaviour. A prospective investigation of the application of the SCJ: Risk to a forensic population detained in conditions of high security was conducted and this demonstrated variation in the predictive utility of the system. The predictive accuracy of subscale items of the SCJ: Risk, and the individual risk factors comprising the subscales of the system were robust for behaviours relevant to violence and suicide/self-harm. However, prediction of behaviours relevant to escape/abscond, vulnerability to risk from others and subversion of security were not demonstrated. The third research strand involved exploration of the preventative utility of the system, specifically if the identification of a patient as high-risk would minimise the occurrence, or prolong the time to an incident of intra-institutional behaviour. Results illustrated the efficacy of the SCJ: Risk system in the identification of high risk individuals for behaviours relevant to any intra-institutional infraction, violence and self-harm. Patients identified as high-risk displayed a higher prevalence and earlier incidence of relevant intra-institutional behaviour. It is concluded that the system of Structured Clinical Judgement: Risk (as an adaptation of the HCR-20) contributes positively to the overall goals of clarity of risk communication, identification and management of high risk patients within forensic psychiatric practice. However, the extended risk assessment of the SCJ: Risk does not make a significant additional contribution to the parental system on which it is based.